Plasmonic silver-based reversible photochromism in Ag+‒doped organomodified silicates-phosphotungstate hybrid films - Noveletto, Julia Cristina; Ferreira-Neto, Elias Paiva [UNESP]; Gonçalves, Lidiane Patricia; Ullah, Sajjad [UNESP]; Donatti, Dario Antonio [UNESP]; Lima Ribeiro, Sidney José [UNESP]; Rodrigues-Filho, Ubirajara Pereira (Elsevier, 2019)
We report novel Ag+‒doped ormosil-phosphotungstate (PW12O40 3−) hybrid films that exhibit reversible yellow photochromism based on the phosphotungstate-assisted photo-induced formation of silver nanoparticles (AgNPs) and their reversible oxidation back to Ag+ ions upon low temperature heating (60–80 °C). The sol-gel derived, dip-coated, hybrid films containing phosphotungstate anions and Ag+ ions exhibit yellow color upon UV exposure and become colorless upon simple heating. Using an array of complementary analytical techniques, we first present a detailed characterization of the prepared materials and then discuss the coloration/discoloration mechanism involved. The presence of both phosphotungstate and Ag+ ions inside the hybrid matrix is found to be imperative for achieving the photochromic behavior. Owing to the presence of AgNPs and their easily achievable coloration/discoloration, these hybrid films may find application in optical memory systems, band pass filters, non-linear optical devices, UV sensing and antibacterial coatings.
Keywords: Ag nanoparticles; Optical thin film; Photochromic; Plasmonic; Polyoxometalate; Sol-gel